Energi terbarukan: analisis kebijakan pemanfaatan biodisel kelapa sawit sebagai bahan bakar nabati nasional di tengah kontroversinya sebagai faktor pendorong deforestasi - Biru, Muhammad Dilheim (Trend and Future of Agribusiness, 2024)
Background: In the midst of the controversy over bioenergy or biofuels as a driving factor for global deforestation, Indonesia is dependent on its palm oil commodities which have been built for years and consume millions of hectares of land. Indonesia's dependence on these commodities to meet domestic and foreign markets is regulated by the biodiesel policy or ESDM Ministerial Decree No. 12 of 2015 concerning the Provision, Utilization and Trading Administration of Vegetable Fuels (Biofuel) as Other Fuels, which states that the use of biodiesel levels in the future will continue to increase, from B20 to B30, then to B40 and so on. However, to be able to meet these policy targets, there is a risk of land clearing. This policy paper discusses what important issues from an economic, social and environmental perspective are related to the development of the palm oil biodiesel industry in Indonesia and what needs to be prioritized in determining future government policy to ensure that sustainable development can be pursued and emission reductions reach targets. Methods: The research method used in this paper is a qualitative approach and descriptive analysis of data collected from literature study. Findings: Apart from that, there are various issues regarding palm oil management, both from a social, economic and environmental perspective, that still need to be addressed, considering that Indonesia is internationally committed to reducing its greenhouse gas emissions by 30% by 2030. Conclusion: Overall In short, there are five recommendations for palm oil biodiesel policy for the future, namely: 1. There is a need for clear data that can support policy decision making; 2. Indonesia needs to evaluate fossil fuel subsidy policies from developing countries that have succeeded in developing their renewable energy sectors; 3. There is a need for intensification, technological improvisation and sustainable agricultural practices on existing oil palm plantation land to meet national bioenergy needs; 4. Prioritizing collaboration between sectors in developing the industry; and 5. The government must be firm in determining a consistent future palm oil biodiesel policy so as not to harm many parties.